STRUCTURAL AND STYLISTIC CHARACTERISTICS OF DETECTIVE STORIES BY G. SIMENON - N. N. Djumon (Гуманитарные и юридические исследования)
Key factor to include a text into detective discourse is detective frame. The most important characteristics of G. Simenon's language are stylistic figures that are based on detective vocabulary and are frequent in writer's prose.